Effect Modification of Multimorbidity on the Association Between Regularity of General Practitioner Contacts and Potentially Avoidable Hospitalisations - Ha, Ninh; Wright, Cameron; Youens, David; Preen, David; Moorin, Rachael (Springer Nature, 2020)
Background: Scheduled regular contact with the general practitioner (GP) may lower the risk of potentially avoidable hospitalisations (PAHs). Despite the high prevalence of multimorbidity, little is known about its effect on the relationship between regularity of GP contact and PAHs. Objective: To investigate potential effect modification of multimorbidity on the relationship between regularity of GP contact and probability of PAHs. Design: A retrospective, cross-sectional study. Participants: 229,964 individuals aged 45 years and older from the 45 and Up Study in New South Wales, Australia, from 2009 to 2015. Main Measures: The main exposure was regularity of GP contact (capturing dispersion of GP contacts); the outcomes were PAHs evaluated by unplanned hospitalisations, chronic ambulatory care sensitive condition (ACSC) hospitalisations and unplanned chronic ACSC hospitalisations. Multivariable logistic regression models and population attributable fractions (PAF) were conducted to identify effect modification of multimorbidity, assessed by Rx-Risk comorbidity score. Key Results: Compared with the lowest quintile of regularity, the highest quintile had significantly lower predicted probability of unplanned admission (− 79.9 per 1000 people at risk, 95% confidence interval (CI) − 85.6; − 74.2), chronic ACSC (− 6.07 per 1000 people at risk, 95%CI − 8.07; − 4.08) and unplanned chronic ACSC hospitalisation (− 4.68 per 1000 people at risk, 95%CI − 6.11; − 3.26). Effect modification of multimorbidity was observed. Specifically, the PAF among people with no multimorbidity indicated that 31.7% (95%CI 28.7–34.4%) of unplanned, 36.4% (95%CI 25.1–45.9%) of chronic ACSC and 48.9% (95%CI 32.9–61.1%) of unplanned chronic ACSC hospitalisation would be reduced by a shift to the highest quintile of regularity. However, among people with 10+ morbidities, the proportional reduction was only 5.2% (95%CI 3.8–6.5%), 9.0% (95%CI 0.5–16.8%) and 17.8% (95%CI 5.4–28.5%), respectively. Conclusions: Weakening of the association between regularity and PAHs with increasing levels of multimorbidity suggests a need to improve primary care support to prevent PAHs for patients with multimorbidity.